THE STUDY OF THERMAL DENATURATION OF BEEF, PORK, CHICKEN AND TURKEY MUSCLE PROTEINS USING DIFFERENTIAL SCANNING CALORIMETRY - Irina V. Agafonkina; Igor A. Korolev; Taras A. Sarantsev (Теория и практика переработки мяса, 2019)
In the temperature range from 45 °C to 90 °C the process of thermal denaturation of a whole complex of muscle proteins in meat takes place. An effective mode to register the thermal denaturation process is the method of differential scanning calorimetry (DSC). As a result of studies the differences during the process of thermal denaturation of muscle proteins of pork, beef, chicken and turkey were defined by the appearance of endothermic peaks in DSC thermograms. The main variances are associated with the process of denaturation of myosin and sacroplasmic proteins and indicate indirectly their quantitative ratio in meat. The values of effective specific heat capacity in the temperature range from 20 °C to 90 °C are obtained as well as those of heat spent on the denaturation process.At reheating, the values of specific heat capacity increased by 0.1 J/(g*K) on the average, and peaks of thermal denaturation were not detected, that certifies the irreversibility of the denaturation process and the decrease in the bound moisture proportion in meat after thermal processing. Knowledge of the nature of protein thermal denaturation of each kind of meat product is one of the necessary tools for developing the technology of meat product thermal processing.